1996
DOI: 10.1126/science.273.5278.1104
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Brightness in Primary Visual Cortex

Abstract: Although neurons in primary visual cortex are sensitive to the spatial distribution and intensity of light, their responses have not been thought to correlate with the perception of brightness. Indeed, primary visual cortex is often described as an initial processing stage that sends information to higher cortical areas where perception of brightness, color, and form occurs. However, a significant percentage of neurons in primary visual cortex were shown to respond in a manner correlated with perceived brightn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
159
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(173 citation statements)
references
References 16 publications
9
159
5
Order By: Relevance
“…The perceived brightness of a surface depends not only on surface luminance but also on the luminance distribution in the surrounding visual field (26, ʈ). It has already been demonstrated in cats and monkeys that single neurons in primary visual cortex exhibit a surround modulation that matches contextual effects in human brightness perception (6,9,27,28). By establishing the dynamics of surface-related responses in early visual cortex, our findings therefore provide the fundamental information necessary for the interpretation of future neuroimaging studies of contextual effects in human subjects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The perceived brightness of a surface depends not only on surface luminance but also on the luminance distribution in the surrounding visual field (26, ʈ). It has already been demonstrated in cats and monkeys that single neurons in primary visual cortex exhibit a surround modulation that matches contextual effects in human brightness perception (6,9,27,28). By establishing the dynamics of surface-related responses in early visual cortex, our findings therefore provide the fundamental information necessary for the interpretation of future neuroimaging studies of contextual effects in human subjects.…”
Section: Discussionmentioning
confidence: 85%
“…Theoretical accounts of surface perception have therefore often postulated a processing of ''filling in'' that mediates creation of surface representations at some level in the visual system (4,5). However, more recent reports suggest that some cells in primary visual cortex do indeed respond to the luminance of uniform surfaces (6)(7)(8)(9)(10). Furthermore, in humans there is a close relationship between perceived brightness contrast and responses in primary visual cortex (11)(12)(13)(14)(15), suggesting that other sensations of brightness may also be encoded in primary visual cortex.…”
mentioning
confidence: 96%
“…Neurophysiological studies of monkey and cat visual cortex provide some support for the filling-in hypothesis. A small proportion of neurons, responding to the interiors of achromatic surfaces, exhibit properties consistent with aspects of human brightness constancy (MacEvoy and Paradiso, 2001), brightness induction (Rossi et al, 1996;Rossi and Paradiso, 1999;Kinoshita and Komatsu, 2001;Peng and Van Essen, 2005), the Craik-Cornsweet-O'Brian brightness illusion (Hung et al, 2001; Roe et al, 2005), and surface completion of the retinal blind spot (Komatsu et al, 2000(Komatsu et al, , 2002. No neurophysiological study, however, has yet revealed evidence of a topographic cortical representation corresponding to uniform surface regions von der Heydt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…How the brain encodes such local and global brightness cues is unknown. Only a few studies have examined neuronal response to uniform surfaces (4)(5)(6)(7)(8)(9). These studies have shown that although cells modulated by luminance change are found as early as the retina and lateral geniculate nucleus (LGN), those modulated by perceived brightness change, which occur independent of actual luminance change over the receptive field (RF), can be found as early as the primary visual cortex (V1).…”
mentioning
confidence: 99%